The Association Between Pain Catastrophizing, Somatization, Psychological Distress and Low Back Pain Severity Among Academics in Malaysia - Mohamad Saufi, Noordiyana Izyanti; Zamri, Eva Nabiha (Makara Journal of Health Research, 2025)
Background: Psychological factors may influence the severity of low back pain (LBP), especially in high-stress professions such as academia. This study aimed to identify the relationship between psychological factors and LBP severity among Malaysian public university academics. Methods: This cross-sectional study aimed to assess the relationship between psychological factors and LBP among academics at four public universities located in the northern region of West Malaysia. A self-administered questionnaire was used to collect information on sociodemographic characteristics, work information, lifestyle factors, LBP presence and intensity, and psychological factors. Data were analyzed using ordinal logistic regression and reported in terms of odds ratio (OR) and 95% confidence interval (CI). Results: Almost half (45%) of the participants exhibited mild to moderate LBP. In the multivariable analysis, mild depression (OR: 2.75; 95% CI: 1.43–5.32), high somatization (OR: 2.90 95% CI: 1.42–5.93), and high pain catastrophizing (OR: 2.03; 95% CI: 1.03–4.01) were significantly associated with greater LBP severity. Conclusions: Our findings emphasized the connection between psychological factors and pain among academics. To address these issues, workplace interventions focusing on pain management, psychological health, and LBP should be implemented, highlighting the necessity for a collaborative effort.